FINANCIAL BOOKKEEPING ASSISTANCE IN A2 MICRO LAUNDRY BUSINESS IN PALEMBANG CITY - RA Rodia Fitri Indriani (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2025)
This research was conducted at Laundry A2 in Palembang City to improve the financial literacy of micro-business actors through simple financial bookkeeping assistance. Many microbusiness actors struggle to systematically record financial transactions, hindering their ability to assess the business's financial condition accurately. Through a participatory approach and on-site training, this activity focuses on the importance of recording daily income and expenses and preparing monthly income statements. The results of the mentoring show that the owners and employees of A2 Laundry are beginning to implement a structured daily bookkeeping system. In addition, the increase in understanding of financial management is evident in the post-test results, which increased by up to 70% compared to the pre-test. A2 Laundry now has a simple income statement that can be used as a basis for business decision-making. The success of this activity shows that a simple bookkeeping model that is tailored to business needs can be implemented effectively by MSME actors. In the future, similar approaches can be replicated in other micro-enterprises to strengthen the financial foundations of local businesses.